Innovation Ecosystems for Teaching Factory Agribusiness: A Strategic Framework - Mahanani, Retno Sari; Prasetyo, Hari; Kurniawan, Bagus Putu Yudhia; Suranto, Dwi Djoko (Indonesian Journal Publisher, 2024)
This study investigates innovation ecosystems within Teaching Factory Agribusiness, addressing the critical gap in the literature regarding the absence of a strategic framework to enhance innovation and sustainability in agribusiness education. Using a grounded theory methodology, we conducted in-depth interviews with 20–30 participants, including educators, industry stakeholders, and policymakers, to gain insights into collaboration, resource sharing, and continuous learning dynamics. The results clarify four thematic areas; (1) Collaboration and Partnerships, (2) Resource Mobilization and Sharing, (3) Policy and Institutional Support, and (4) Continuous Learning and Adaptation. The above threads weave together into a framework to make agribusiness education explicit in the functioning of innovation ecosystems. The findings have significance for policy-makers, educationists, and industry personnel involved in improving the quality of agribusiness innovation. Future research directions can be a framework, especially regarding the benefits of innovation, and collaboration through technological facilities.